Hidden Hate, Hidden Violence: Dismantling Myths and Identifying Fresh Challenges for Research and Policy - Chakraborti, Neil (Journal of interpersonal violence, 2024)
Hate crime has become an increasingly familiar term within global scholarship, with advancements in conceptual understanding and empirical knowledge helping to generate improved policy responses across many parts of the world. However, the continued demonization of 'other' identities, the escalating volume of hate incidents worldwide and the prevailing climate of rising tensions, decreasing resources and political de-prioritization all suggest that many urgent challenges remain. Contributors to this special issue have dismantled common stereotypes and misperceptions which hamper our collective capacity to address contemporary expressions of hate and violence. In doing so, they draw from their research evidence to identify “hidden” challenges which should be at the forefront of attempts to address the causes, effects, and prevention of all forms of violence. This call for reconfiguration is the unifying theme which runs through each article, and which paves the way for more nuanced analyses that offer new frameworks for responding to the diverse and changing patterns of violence. These are challenges which straddle disciplinary boundaries, geographical borders, and the physical/digital world, and which demand the international, intersectional, and interdisciplinary perspectives evident within this special issue.